Beware! A simple renal cyst could be a hydatid cyst - Nidhi Sehgal; Vinod Priyadarshi (Urology Annals, 2017)
Kidney is one of the most common sites for the cyst formation in the body, and the management of simple cysts is required entirely for its symptoms and complications. Surgical decortication is an established treatment for a large and symptomatic simple renal cyst. On the other hand, hydatid cysts of the kidney are usually multiloculated complex or calcified cysts and are quite rare.[2]Their surgical treatment also differs and requires complete excision with pericystectomy or partial/complete nephrectomy depending upon residual functional parenchyma, using extreme caution to avoid spillage, recurrence or development of severe anaphylactic shock.[3]A simple cyst harboring a hydatid cyst is highly uncommon and quite dangerous; as if not diagnosed preoperatively, it can create huge trouble for both the patient and the operating surgeon which happened in the present case.